PVDF-HFP/NKBT composite dielectrics: Perovskite particles induce the appearance of an additional dielectric relaxation process in ferroelectric polymer matrix. (April 2021) - Pavlović, Vera P.; Tošić, Dragana; Dojčilović, Radovan; Dudić, Duško; Dramićanin, Miroslav D.; Medić, Mina; McPherson, Michael M.; Pavlović, Vladimir B.; Vlahovic, Branislav; Djoković, Vladimir
Abstract: Na0.25 K0.25 Bi0.5 TiO3 (NKBT) perovskite particles are synthesized by solid-state method and used as a filler for polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) co-polymer. X-ray diffraction analysis of NKBT powders shows that the particles have a rhombohedral perovskite crystal structure (R3c symmetry). Raman spectroscopy reveals that the co-polymer crystallizes predominantly into the mixture of polar β- and γ-crystals, while there is also a contribution of the non-polar α-crystal phase. The introduction of the NKBT into the PVDF-HFP results with an increase in effective dielectric permittivity and this effect depends on the inorganic content in the composite. The most interesting result of the present study is that the introduction of NKBT particles induces the appearance of an additional transition peak in the dielectric spectra of the co-polymer matrix. At the fixed frequency of ~2 kHz, the observed process appears at ~10 °C (about 45° above the glass transition temperature) and its magnitude strongly depends on the amount of the NKBT in the composite. Dielectric spectroscopy measurements of the composites are carried out in the wide range of frequencies (from 0.1 Hz to 1 MHz) and temperatures (from −100 to 100 °C). They reveal that the novel process can be clearly distinguished in the frequency range between 160 Hz and ~50 kHz. Highlights: Na0.25 K0.25 Bi0.5 TiO3 (NKBT) perovskite particles are synthesized by solid state method. PVDF-HFP/NKBT composite films were prepared by solution mixing. NKBT particles induce an increase in effective dielectric permittivity of the films. An additional transition peak was observed in the dielectric spectra of the composite film. The magnitude of the novel transition depends on the NKBT content.